The Structural Evaluations of SARS-CoV-2 Main Protease (Mpro): A Review for COVID-19 Antivirals Development Strategy - Muhammad Hamzah Syaifullah Azmi; Ernawati Arifin Giri-Rachman (3BIO: Journal of Biological Science, Technology and Management, 2023)
It has been almost four years since the first case of COVID-19 emerged, and the antivirals that could work specifically against SARS-CoV-2with a high efficacy are still under development. Main Protease (Mpro) of this virus plays a crucial role in virion maturation during itsreplication within the host cell. This protein works together with the papain-like protease (PLpro) to cleave polyprotein 1a  and 1ab  into a total of16 functional fragments of non-structural protein. Antiviral with the ability to inhibit the activity of Mpro could potentially prevent the virion replication, and they can be developed to target the catalytic or allosteric site of this protein. Antiviral that works on the catalytic site will act as competitive inhibitors of the substrate peptide which leads to the loss of Mpro function. Targeting the allosteric site (e.g. distal site and dimerization interface) will cause allosteric modu- lation of the protomer which could alter the protein 3D conformation and disrupt the formation of homodimer structure. This will affect the geometry and surface structure of the catalytic site which in turn decreases the affinity of the substrate peptide towards the Mpro catalytic site, resulting in a completeinactivation of the protein. Mutation study of Mpro amino acids sequence also reveals that the mutation frequency for each amino acid position isextremely low and negligible. Moreover, it is found that this protein has 24 mutational cold spot residues scattered within its structure which could be targeted for the development of antivirals due to its highly conserved nature.